PENERAPAN BIMBINGAN KELOMPOK TEKNIK SELF MANAGEMENT DALAM MENGATASI KEJENUHAN BELAJAR PADA SISWA SMP 2 NALUMSARI JEPARA - Agung Listyansyah (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2024)
Study saturation is a condition in which students of SMP 2 Nalumsari Jepara feel physically and psychologically tired, which is marked by a lack of concentration or listening to what the teacher says; not willing to teach assignments (PR), quickly forget the lesson; learning outcomes achieved will not be maximal; slow in managing the information (lessons) delivered by the teacher; low enthusiasm for learning, either at school or at home. The objectives to be achieved in this study are as follows: (1) Describe the application of self-management technique group guidance in overcoming learning saturation in SMP 2 Nalumsari Jepara students. (2) Describing the alleviation of learning boredom in SMP 2 Nalumsari Jepara students by implementing self-management technique group guidance.